THE DESIGN OF THE SOUTH NIAS CULTURAL CENTER WITH A NEO-VERNACULAR APPROACH - Angelus Manao; Ramadhani Fitri; Novalinda (INFOKUM, 2022)
Tourism has now become the prima donna of the world and a source of income for several countries in the world. Increasing tourism destinations and investment, making tourism a key factor in export earnings, job creation, business and infrastructure development. Currently, Nisel has its own annual agenda to increase its tourism. However, the existence of buildings to accommodate all these activities is still very minimal. The design of the South Nias Cultural Center is a building design response to the need for new facilities in South Nias Regency, especially in the arts and culture fields. Coupled with the application of the Neo-Vernacular approach, this design is a process of inculcating cultural values ​​in a building design for the South Nias Cultural Center. With the existence of the South Nias Cultural Center, The longing to witness various cultural events and traditional arts of South Nias will be fulfilled even more due to the new facilities that are more organized and organized. In addition, the South Nias Cultural Center is expected to become a new tourism icon in South Nias Regency, especially on the Baloho beach and take part in advancing South Nias tourism in the future.